Microcredit, Technology Adoption And Economic Development Of Rural Household - Jumbri, Isma; Mohd Nasir, Nabilah Najah; Mohamad Sharif, Sabri; Ismail, Albert Feisal; Zainuddin, Mohamad Zahir (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
The main objective of this study is to investigate whether or not Amanah Ikhtiar Malaysia (AIM) microcredit has led to the technology adoption and increase of rural household economy, particularly in monthly household income of its participants. This study was conducted in Melaka on 200 participants. The findings of the study showed that the AIM microcredit had a significant impact on technology adoption and increased the participants’ monthly household income in Melaka. The findings suggested that AIM microcredit remained relevant and played a vital role in increasing rural household monthly income, inculcated entrepreneurship among women and reduced poverty. Therefore, the Malaysian government should enact the relevant policies and provide support to enhance the effectiveness and outreach of microcredit.